Serum Ischemia-Modified Albumin Concentration and Ischemia-Modified Albumin/Albumin Ratio in Hyperemesis Gravidarum - Fatma Beyazıt; Eren Pek; Hakan Türkön (Haseki Tıp Bülteni, 2018)

(untitled)
Aim:Hyperemesis gravidarum (HEG) is characterized by severe nausea and vomiting, weight loss and nutritional deficiency. Although exact cause of this condition is still a matter of debate, contribution of oxidative stress to pathogenesis of HEG was demonstrated in some studies. The aim of this study was to investigate the diagnostic value of ischemia-modified albumin (IMA) concentration and IMA/albumin ratio (IMAR) in HEG patients.Methods:One patient group and two control groups were constituted. Pregnant subjects with HEG were included in HEG group (n = 31) and age-, gestational age-, and body mass index (BMI)-matched healthy pregnant women in control group (n = 30). The second control group was constituted from age- and BMI-matched non-pregnant women (n=30). Serum IMA, IMAR blood glucose, albumin, urea, creatinine, alanine aminotransferase and aspartate aminotransferase levels were measured in all subjects.Results:Serum median IMA levels [0.55 (0.43-0.68)] was found to be elevated in HEG patients compared with pregnant [0.52 (0.34-0.61)] and non-pregnant controls [0.48 (0.27-0.57)] (p=˂0.001). IMAR levels were also found to be significantly elevated in HEG patients compared to both control groups. According to correlation analysis, IMA and IMAR levels were only correlated with C-reactive protein levels.Conclusion:Elevated levels of IMA and IMAR in HEG patients might be due to ischemic intrauterine environment.